Type of attitude to the disease in patients with epilepsy and suicidal ideation - N. I. Shova; V. A. Mikhailov; E. A. Granovskaya; V. V. Bocharov (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Suicidal behavior is characterized by the response of the individual to the conditions of the crisis situation experienced. The unrelenting interest of researchers around the world is aimed at studying the factors that determine the risk of suicidal intentions in patients with epilepsy.Purposal. To determine the main types of attitude to the disease in patients with epilepsy and suicidal thoughts.Materials and methods. 112 patients with epilepsy were examined and divided into 2 groups depending on the presence of suicidal thoughts at the time of the study: 1st group – with suicidal intentions, 2nd group – without it. The method «Type of attitude to the disease» were used.Results. Thus, among the clinical factors of suicidal risk in patients with epilepsy, severe course of the underlying disease is the most significant, which is manifested by frequent seizures, serial course, and drug resistance form. It was revealed that patients with epilepsy with suicidal thoughts are characterized by the presence of «mixed» and «diffuse» types of attitude to the disease, with a predominance of maladaptive forms. The analysis of «pure» types of attitude towards the disease in two groups showed that there are fewer respondents with a «pure» type of attitude towards the disease in the group of patients with suicidal thoughts than in the group of patients without it. Along with the ergopathic and sensitive types, in the 2nd group of patients, the anosognosic type of attitude to the disease is also quite pronounced, and in the 1st group, patients with anosognosic, anxious and hypochondriacal types of attitude to the disease were identified.Conclusion. Consequently, patients with epilepsy are characterized by: vulnerability, vulnerability, concern about possible adverse impressions that they can make on others with information about their illness; the desire, despite the severity of the disease, to continue working; lack of criticality to their own disease, which can lead to destabilization of the underlying disease and the formation of suicidal behavior.